Design, qualification and Shariah governance of stock screening methodologies in selected Gulf Cooperation Council (GCC) countries in comparison with the United States - Kasi, Umayal; Muhammad, Junaina (Emerald Publishing, 2018)
Purpose This paper aims to compare and analyse the aspects of Shariah screening methodologies within the selected Gulf Cooperation Council (GCC) countries as well as comparing the methodologies with the USA, and to examine how Shariah screening methodologies affect financing and investing activities of a firm.